Handloom Industry in Karnataka - Part-1 - (:unkn) unknown (My University, 2023)
"Clothes are as inevitable to man as food itself and so, garments are his constant companion. Weaving and rolling thread has a tendency to produce a variety of forms, colors and the glory to embellish the human body with even fresh glow. The design of dress and color changed according to personality and lifestyle and even culture and tradition are interwoven with these. Years of experience declare the textiles and the material they weave to have changed in the heat of the climate, environment, region and even religion. Since the very beginning the process of weaving clothes has been modified over time. The handloom cot has changed the source of livelihood for thousands of families and has supported them as their backbone for growth and development. Handlooms are believed to have been discovered by Westerners around 8000 years ago, but still no concrete evidence is there for when and where handlooms actually began. The family belonging to communities like Deevanga, Thogataveera, Pancamassali, Settigaar, Kuruhina Setty in Karnataka had mastered the art of weaving and even other weaving communities are encouraged to weave everyday. There is another handloom weaving community known as “Sokkula Sali.” Specific families carry out this responsibility and families who have made weaving a profession work can be seen in all the villages in Karnataka. More than half a crore people depend on weaving in Karnataka. Handloom cloth production grew significantly from Chamarajanagarto to Bidar. Handlooms are solely dependent on human labor, from the weaving on the loom, coloring the thread, and preparation of the dress, all are drawn from sweat. The whole process of hand weaving is as complex as the weaving industry. The making of handloom clothing involves two stages: the preparation of the cotton for weaving in three rooms and the work that follows in a post room The process of cleaning cotton is called count, high count is used in the production of saree. The most significant phase in coloring of the thread and almost all weavers chose synthetic colors today. Tie and dye coloring method requires waste rubber tube tied to the thread and different colors are applied to the thread after washing one after another color in water and up to four times, a variety of methods like triloom, vertical frame room, land room, tribal room, blanket room are used to weave. Old types of handlooms are called “Lion” and “vertical looms''. Lion types are specialized for weaving ladies wear. Vertical looms are used to weave carpets, mats etc. Now we have fly shuttles and frame looms which are widely in use everywhere. Further they are modified as “Dobbin'', ''barrel” and ''Latis dobbin”. Earlier looms were equipped with ‘tapit’ which had a lax and was similar to a chain to create designs and the designs were very limited. After the introduction of ‘Jacquard’ looms, a vast variety of designs could be formed and now many looms are equipped with Jacquard looms and are also able to create ‘tapit’. Further ‘jacquard’ has been modified in 120, 240 and 480 Jacquard. Using 480 Jacquard it is possible to create more and more designs”. Earlier artists were hired for creating designs now as the 'card punching’ system has been introduced, now they do not use any such old looms.” At Least 1000-2000 cards are needed in making saree. In Karnataka, Chintamani has uniqueness for its collection of Saris and is called “Chintamani Silk Saris.” In Ilkal it is called ‘Ilkal saree’. In Molakalmuru it is called as ‘Molakalmuru Saris’, In Bangalore, there are specific areas which produce saris according to the existing trend and also try to keep pace with the changing trends.” "
Keywords: Handloom Industry in Karnataka; Handloom Weaver; Sokkula Sali and Padma Sali Community; Charaka; Blanket; Dobbin Loom; Kannada